POLA PENCARIAN INFORMASI TENTANG REPRODUKSI SEKSUAL PADA MAHASISWA UNIVERSITAS SRIWIJAYA - Nurly Meilinda; Sena Putra Prabujaya; Krisna Murti (Jurnal Riset Komunikasi, 2018)
This study aims to determine the sexual reproduction information seeking pattern of Students in Sriwijaya University. It uses a qualitative approach based on Wilson's Model of Information Seeking Behavior that consist; passive attention, passive search, active search, and ongoing search. This research involves in-depth interviews with 12 students of Sriwijaya University. The study found that students at Sriwijaya University tend to perform a passive search pattern in seeking of sexual reproductive information. However this conditions does not apply when the students have responsibilities to fullfil, both academically and professionally, as it is known that the student with such responsibilities will perform an active and ongoing search. The study also found that Wilson's Search Information Behavior model can still be usefull. In the context of information seeking behavior of Student in Sriwijaya University, it was still influenced by psychological conditions, demographics, roles in society, environment, and characteristics of information sources. This study also identifies the motive of sexual reproduction information seeking behavior in students at Sriwijaya University.